Faktor-Faktor yang Mempengaruhi Kejadian Insomnia pada Lansia di Posyandu Lansia Wilayah Kerja UPTD Puskesmas Puncu Kabupaten Kediri - Ajeng Wahyu Ningsih; Dodik Arso Wibowo (STIKES Karya Husada Kediri, 2018)
Insomnia in the elderly is a condition where an individual experienced a change of the quantity and quality of the pattern of breaks which cause discomfort interfere with desirable lifestyle. Most of the elderly have high risk of experiencing sleep disorders due to several factors. Some factors which influence insomnia such as age, gender, psycology, environment and lifestyle. Design of the study used descriptive, this research June 04th, 2018, there are 18 respondents by using purposive sampling, the instrument is used questioner, the research variable is used to know the factors that influence insomnia of elderly, the data were analyzed by percentage and interpreted with the quantitative. The result of the study on age factor there are 4 respondents (22%) got insomnia aged 60-65years old, there are 8 respondents (45%) got insomnia aged 66-70 years old, there are 6 respondents (33%) got insomnia aged 71-74 years old, there are 18 respondents (100%) gender factor got insomnia, on psychological factor there are 14 respondents (78%) have negative psycology, there are 12 respondents (67%) have physical illness, 11 respondents (61%) get environmental factors and there are 12 respondents (67%) have positive life style. There fore it is expected that the elderly can avoid the cause of in insomnia and improve quality and quantity of sleep better. The elderly can do relaxation techniques and ritual activities before going to bed. The result of the study can be concluded if those factors can influence the quality and quantity of sleep of elderly.